Islamic Banking Services for Communities and Families in Aceh Province Post Closure Of Conventional Banks: A Comprehensive Review - Maulana, Muhammad; Jihad, Azka Akmalia; Fildzia, Ayrin Sazwa; Ramly, Arroyyan; Shabarullah, Shabarullah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Following the enactment of Qanun No. 13 of 2018 concerning Islamic Financial Institutions, some people believe that the closure of conventional banks in Aceh, without viable alternatives, has caused confusion. This is primarily because people were accustomed to using conventional banking facilities for various transactions, both at local, national, and international levels. This study aims to assess the performance of Islamic banks in Aceh after the implementation of Qanun No. 11 of 2018, which replaced conventional banks that had previously provided optimal services to the community. Specifically, the study examines the actions and strategic steps taken by Islamic banks in Aceh to meet the banking needs of the community. It also explores whether the performance and product diversification of Islamic banks have impacted customer satisfaction following the implementation of Qanun No. 11 of 2018 in Aceh. Data was collected through interviews with 23 informants. The findings suggest that while Islamic banks continue to provide services and meet community needs after the conversion, customers still face some technical obstacles, which may give the impression that Islamic banking services are not yet fully effective. However, improvements in post-conversion services appear to be aligned with the regulations set by the government.